2013
DOI: 10.1038/nature12807
|View full text |Cite
|
Sign up to set email alerts
|

Muc5b is required for airway defence

Abstract: Respiratory surfaces are exposed to billions of particulates and pathogens daily. A protective mucus barrier traps and eliminates them via mucociliary clearance (MCC)1,2. However, excessive mucus contributes to transient respiratory infections and to the pathogenesis of numerous respiratory diseases1. MUC5AC and MUC5B are evolutionarily conserved genes that encode structurally related mucin glycoproteins, the principal macromolecules in airway mucus1,3. Genetic variants are linked to diverse lung diseases4-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
597
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(634 citation statements)
references
References 52 publications
29
597
1
7
Order By: Relevance
“…This airway mucus is composed mainly of mucin glycoproteins and water, and provides a matrix for a wide variety of antimicrobial molecules including antibodies, defensins, protegrins, collectins, cathelicidins, lysozyme, histatins and nitric oxide21, 22, 23. When the mucus barrier has increased viscosity making it resistant to mucociliary clearance, or when the barrier is deficient or depleted, the risk of opportunistic microbial infection is increased 24. Mucins, primarily MUC5B, are tonically secreted by the nonciliated airway epithelial surface cells, known as club cells in the small airway, and can be released in large amounts in response to inhaled material by submucosal gland mucous cells, which contain large numbers of mucin granules ready for stimulated secretion 22…”
Section: Introduction To Oxidative and Er Stressmentioning
confidence: 99%
“…This airway mucus is composed mainly of mucin glycoproteins and water, and provides a matrix for a wide variety of antimicrobial molecules including antibodies, defensins, protegrins, collectins, cathelicidins, lysozyme, histatins and nitric oxide21, 22, 23. When the mucus barrier has increased viscosity making it resistant to mucociliary clearance, or when the barrier is deficient or depleted, the risk of opportunistic microbial infection is increased 24. Mucins, primarily MUC5B, are tonically secreted by the nonciliated airway epithelial surface cells, known as club cells in the small airway, and can be released in large amounts in response to inhaled material by submucosal gland mucous cells, which contain large numbers of mucin granules ready for stimulated secretion 22…”
Section: Introduction To Oxidative and Er Stressmentioning
confidence: 99%
“…In mouse lungs, MUC5B and MUC5AC are expressed primarily in club cells (1,10). Mice with a disrupted Muc5b gene accumulated mucus in the upper airway, whereas mice with a disrupted Muc5ac gene lacked apparent respiratory abnormalities (10). Together, these results suggest that MUC5B and MUC5AC may have different functions.…”
mentioning
confidence: 95%
“…In human airways, MUC5B is produced in submucosal glands and goblet cells, and MUC5AC is produced in goblet cells (1,4,5,9). In mouse lungs, MUC5B and MUC5AC are expressed primarily in club cells (1,10). Mice with a disrupted Muc5b gene accumulated mucus in the upper airway, whereas mice with a disrupted Muc5ac gene lacked apparent respiratory abnormalities (10).…”
mentioning
confidence: 99%
“…A previous study on mice demonstrated that MUC5B mucin deficiency is associated with MCC dysfunction and causes difficulty in biodefense of the airway. 10) However, overproduction of MUC5B or MUC5AC mucin causes narrowing of the airway. A primary symptom of patients with COPD and asthma is hypersecretion of airway mucus with hyperplasia and it causes airflow limitation.…”
Section: Discussionmentioning
confidence: 99%
“…It shows a small increase in the airway of patients with respiratory diseases, but it is required for biodefense of the airway, with a lack of MUC5B inducing inefficient MCC. [8][9][10] MUC5AC production is regulated in various ways, such as by inflammatory cytokines (interleukin-1β, tumor necrosis factor-α), cell-cell adhesion molecules, and EGF receptors. 11,12) However, little is known about the regulation of MUC5B production.…”
mentioning
confidence: 99%